Negotiating tensions in identity: from physical education teacher educator to academic leader. Issue 6 (24th July 2022) - North, Chris; Patton, Kevin; Coulter, Maura
ABSTRACT: Academics in Physical Education Teacher Education (PETE), similar to their counterparts in other disciplines, receive little formal preparation when they take on academic leadership positions. Yet such career changes require different skill sets and expose academics to complex challenges of leadership. We (three academics) initiated this study to explore the implications of academic leadership positions for our PETE identities. We wished to unpack the consequences of taking on these leadership roles, or our 'desire to become more' and 'to better understand' (Ovens, A., & Fletcher, T. (2014). Doing self-study: The art of turning inquiry on yourself. In A. Ovens & T. Fletcher (Eds.), Self-study in physical education teacher education: Exploring the interplay of practice and scholarship (Vol. 13, pp. 3–14). London: Springer, p. 7). This research used a collective self-study methodology and drew on Skype meetings, reflections, critical friend prompts and emails. We present our findings as coming to view identity changes as tensions: bridging between roles; competing identities; identity as stable or malleable; and educator or fiscal manager. Gee's four identity perspectives including natural, institutional, discursive and affinity are used to unpack these tensions. While challenges associated with our role change persist, collective S-STEP was critical to understanding ourselves, the tensions experienced, and navigating the gaps between PETE and academic leadership.